2013
DOI: 10.3109/10428194.2013.776680
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral T-cell lymphomas: analysis of histology, staging and response to treatment of 208 cases at a single institution

Abstract: Peripheral T-cell lymphomas are characterized by a poor clinical outcome. We retrospectively analyzed 208 adults treated in our institution between 2000 and 2011. Median age at diagnosis was 55 years. Fifty-one percent had B symptoms and 51% serum elevated lactate dehydrogenase (LDH) levels. Eastern Cooperative Oncology Group (ECOG) performance status (PS) was 0-1 in 63% and 2-4 in 37%. According to Ann Arbor classification, 16% were at stage I-II and 84% at stage III-IV. Histological subtypes were: 39% periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Commonly, CHOP (cyclophosphamide, doxorubicin, vincristine, prednisone) is the “go-to” chemotherapy regimen of choice for PTCL (Broussais-Guillaumot et al, 2013), despite evidence that, except for ALCL, ALK+, it is largely ineffective, as evidenced by a large retrospective analysis from the German High-Grade Non-Hodgkin Lymphoma Study Group (Schmitz et al, 2010). In this analysis, 343 patients with a diagnosis of PTCL were treated with six to eight cycles of CHOP or CHOP plus etoposide (CHOEP).…”
Section: Frontline Therapymentioning
confidence: 99%
“…Commonly, CHOP (cyclophosphamide, doxorubicin, vincristine, prednisone) is the “go-to” chemotherapy regimen of choice for PTCL (Broussais-Guillaumot et al, 2013), despite evidence that, except for ALCL, ALK+, it is largely ineffective, as evidenced by a large retrospective analysis from the German High-Grade Non-Hodgkin Lymphoma Study Group (Schmitz et al, 2010). In this analysis, 343 patients with a diagnosis of PTCL were treated with six to eight cycles of CHOP or CHOP plus etoposide (CHOEP).…”
Section: Frontline Therapymentioning
confidence: 99%
“…CHOP (cyclophosphamide, doxorubicin, vincristine and prednisone) or CHOP-like regimens are most commonly used first-line treatments in patients with PTCL. However, outcomes are poor with complete remission (CR) of about 50% and 5-year overall survival of only 25-45% 1,2. Although prognostic indicators such as the international prognostic index (IPI) and the prognostic index for T-cell lymphoma (PIT) have been proposed in PTCL, their prognostic values are not well established 3-6.…”
Section: Introductionmentioning
confidence: 99%
“…This trend was not observed for AITL and ATLL. Since the international prognostic index (IPI), presence of B-symptoms, and the expression of cytotoxic molecules are currently recognized as prognostic factors in PTCL-NOS, [35][36][37][38] we simultaneously integrated these known prognostic markers and TERT expression in a multivariate analysis to show the risk of each factor (Table 2). The analysis found that IPI was an independent poor prognostic factor; however, other factors, including TERT expression, were not independent prognostic factors.…”
Section: Clinical Significance Of Tert Expressionmentioning
confidence: 99%